Students’ Perceptions on the Implementation of Natural Product Chemistry Laboratory Using Sasambo Medicinal Plants - Hakim, Aliefman; Jufri, A. Wahab; Jamaluddin, Jamaluddin; Ramandha, Muhammad Eka Putra; Sari, Indah Juwita; Alasa, Victor M. (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
This research described the implementation of the natural product chemistry laboratory using Sasambo medicinal plants (Sasak, Samawa, Mbojo, indigenous tribes of Nusa Tenggara Barat Province, Indonesia). It revealed students' perceptions of laboratory activities. The use of Sasambo medicinal plants in laboratory activities is carried out because it is very close to students' daily lives. This research method was descriptive qualitative obtained from observation, documentation, interview, and questionnaire techniques. Respondents consisted of 59 third-year students from the Department of Chemistry Education at one of the state universities in Nusa Tenggara Barat, Indonesia, during the second semester of the 2020/2021 academic year. This laboratory activity begins with giving a laboratory project to students. The team determined the Sasambo medicinal plant species used in this laboratory based on the results of the previous isolation. The selection of the Sasambo medicinal plant species took into account the difficulty level of isolation of its secondary metabolite compounds. The results showed that the planning of the natural product chemistry Laboratory using Sasambo medicinal plants was in a good category. The facilities and infrastructure used were complete and proper, the learning resources used were apt and up-to-date, and the implementation of the activities was in the good, interesting, and disciplined category.